Magnetic Contactless Crank-rocker Machine - Adnan Ishtay; Mohammad Awwad Al-Dabbas (Ital Publication, 2022)
Objective: In this paper, a proposed technique of motion transmission is introduced, which is based on the crank-rocker principle of motion. The energy transmission action is performed through magnetic force, in which no direct connection is made between the energy source input and the energy load output. Also, to illustrate the concept of motion and to approve the continuity of energy transmission using this proposed technique, a simple model of this mechanism has been built and run, showing the basic sequence of operation. Methodology/analysis: In this mechanical transmission mechanism, one side is rotating and the other side is vibrating, in which any side is energy input (which is usually the vibrating rocker), and the other side is energy output (which is the rotating crank). That seems similar to the classical crank-rocker machine in the four-bar mechanism, but without direct mechanical contact between the input and output energy stream. The concept of motion and mathematical analysis with structuring conditions is provided in this paper, where the dynamic analysis of the system is left for future work. A pilot physical prototype is manufactured and experimentally tested, validating the proposed design. Findings: The structural parameters of this proposed contactless crank-rocker machine have been modelled and simulated using the MATLAB program. It shows that these parameters could be selected and optimized to guarantee the minimum conditions for continued energy transmission. Based on these parameters, a simple model has been built and operated, which illustrates the concept of motion and validates the finding of MATLAB simulation. Novelty/improvement:Contactless crank-rocker motion is a very promising technique. It is possible to apply it in many applications, like the energy harvesting area, and it could be employed certainly in specific designs, such as MEMS, where no other motion transmission types can be used. Doi: 10.28991/ESJ-2022-06-02-07 Full Text: PDF